Analysis of the Level of Taxpayer Compliance with Indonesian Tax Law for Women With Marital Status - Yohanes Mardinata Rusli; Muhamad Habib; Irwan; Parlindungan Banjarnahor; Jetro Sihombing (Journal of Law, Politic and Humanities, 2025)
This study analyzes the factors that influence the behavior of compliance with the Tax Law applicable in Indonesia for female individual taxpayers with marital status. These factors are analyzed from the level of Taxpayer Knowledge, Taxpayer Awareness and Tax Morale who do freelance work in the city of Jakarta. This study also analyzes Tax Morale as a moderator for the influence of Tax Knowledge and Tax Awareness on Tax Compliance. The population in this study are female Taxpayers with marital status registered at the Tax Service Office at the Regional Office of the Directorate General of Taxes in the city of Jakarta with the areas of West Jakarta and North Jakarta. The type of data used in this study is primary data obtained from distributing questionnaires to respondents who are the samples that have been determined in this study. Analysis of the results of this study test shows that Tax Knowledge and Tax Awareness have a positive and significant effect on the behavior of taxpayer compliance of female individual taxpayers with marital status. While Tax Morale as a moderating variable strengthens the influence of Tax Knowledge and Tax Awareness on the Behavior of Tax Compliance of female individual taxpayers with marital status. This research is expected to provide a reference to the Directorate General of Taxes (DJP) of the Ministry of Finance of the Republic of Indonesia to find out the behavior of Individual Taxpayers, especially women with marital status, that the level of taxpayer awareness must be increased, especially by providing socialization and education about the Tax Laws in force in Indonesia.